A note on the use of nomograms for apparent resistivity computation - Chan, S.H. (Wiley, 1971)
Nomograms are presented for the purpose of rapid computation of the apparent resistivity functions from the field data for symmetrical and unsymmetrical linear electrode arrays. Copyright © 1971, Wiley Blackwell. All rights reserved